Effect of Ocimum basilicum L. and Eucalyptus camaledulensis Dehn. powders on Cowpea weevil ( Callosobruchus maculatus F.) in stored cowpea - Elsiddig, Fathelrahman I.; Elneel, Mohamed H. Hamad (Al-Mukhtar Journal of Sciences, 2017)
A laboratory experiment was carried out during the period June – September 2011 at Abu Naama Faculty of Agriculture - University of Sinnar, Sudan, to study the effect of different powdered preparations of leaves and flowers of Rehan and leaves of Cafure on cowpea weevil (Callosobruchus maculatus Fabric.). The experiment was laid out as a complete randomized design (CRD) with four replicates. Different concentrations of the two tested plants were formulated by weight from 2 kg of cowpea seeds to give the following treatments: Rehan leaves powder 5% and 10%, Rehan flowers powder 5% and 10%, Cafure leaves powder 5%, and 10%, and untreated control. The treatments were added to clean cowpea seeds. Number of eggs, number of adults, and 100 seed weight were recorded every two weeks up to the end of the experiment. Results indicated that Rehan and Cafure powders of the two concentrations 5%, 10% significantly reduced the number of eggs and adults of cowpea weevil Callosobruchus maculatus up to 12 weeks compared to the untreated control. Results also indicated that starting from the 4th week up until the10th week; all treatments of 10% concentration were significantly different from the untreated control in term of 100 seed weight. Results concluded that the performance of the tested preparations will still encourage the inclusion of these products in IPM programs with other natural and biological measures.